Analyzing The Ideological Foundations of Islamic Education at Pondok Pesantren Islamic Center Bin Baz Yogyakarta - Abdullah, Soehardin; Sukiman, Sukiman; Machali, Imam (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Education plays a crucial role in ensuring a nation's continuity, with Islamic education being particularly significant as it derives knowledge from the Qur'an and Hadith, aiming for success in both worldly life and the afterlife. Following Indonesia's reform era, diverse Islamic religious education institutions emerged, each with distinct ideological backgrounds. This research aims to: 1) Analyze the theoretical foundations and application of Islamic values in education; 2) Describe the theoretical foundations of social networks and organizations; 3) Construct the ideological theory of education and its diverse manifestations; 4) Analyze the role of ideological movements in shaping Islamic education and their impacts. Using a qualitative method, the study focuses on the Islamic Education institutions of the Majelis At-Turots Al-Islamy Foundation, specifically Pondok Pesantren Islamic Centre Bin Baz (ICBB) Yogyakarta. Data analysis involves collection, reduction, presentation, and conclusion drawing. Islamic education, rooted in lifelong learning from the Qur'an and Hadith, is driven by juridical and ideological foundations, encompassing Aqidah, Ibadah, and Moral/Akhlak values. Ideological movements in post-reform Indonesia are categorized into Modernist, Traditionalist-Conservative, Transformist, and Fundamentalist Islam.